Analisis Kumpulan Unsur Platinum (Pge), Nikel (Ni) Dan Kromium (Cr) Di Tapak Prasejarah Bukit Bunuh, Lenggong, Perak Untuk Pembuktian Impak Meteorit - Abdullah, Abdul Mutalib (2021)
Bukit Bunuh prehistoric site (BBH) was found in 2001 during a palaeoenvironmental survey by Centre for Global Archaeological Research USM. BBH is situated at 100° 58’ 05” East dan 5° 04’ 05” North.BBH revealed the meteorite impact event and Paleolithic stone tools through the megascopic, macroscopic, and microscopic evidence. The purpose of this study is to determine the concentration of siderophile elements such Platinum Group /PGE (Os, Ir, Ru, Rh, Pt, Pd, and Re), Nickel (Ni), and Chromium (Cr) in BBH rocks. The methods used are X-Ray Fluorescence (XRF), Neutron Activation Analysis (NAA), and Inductive Couple Plasma-Mass Spectroscopy (ICPMS). 20 impact-related rocks from inside the crater such as impact melt, seuvite, metasediment impact, quartz impact, & granite impact and six (6) target rocks from outside the crater such as slate, limestone, granite biotite, syiz quartz, red quartz and grey quartz were analyzed. The results showed some significant concentration of PGEs compared to the continental crust concentration. For an example, concentration of iridium (Ir) inside the crater is 0.3 ppb, which is 10 times higher than the bulk continental crust value (0.022 ppb).